ANALYSIS OF RISK-TAKING POLICY CHANNEL ON INDONESIAN BANKING - Ramadhan, Ferdy Gerry; Benardin, Benardin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
The purpose of this study is to explore how monetary policy influences the risk-taking of banks their performance in Indonesia. The study measures the risk-taking policy channel, which is the way that monetary policy affects the risk preferences and actions of banks. The study uses five indicators: ROA, FDR, BOPO, NPL, and M2. The study applies VECM to examine the data from 2010 to 2021. The findings reveal that Variables ROA, FDR AND BOPO have short-run and ROA, NPL, M2, and FDR correlated with each other in the long run. The findings also show BOPO is only significantly correlated with M2 in the long run. This means that loose monetary policy lowers the profitability, liquidity, and efficiency of banks, and raises the credit risk. The study recommends that monetary policymakers should take into account the risk-taking of banks when setting monetary policy, and that banks should handle their risks carefully to sustain their performance.